Karakterisasi Fisis dan Laju Pembakaran Briket Sebagai Energi Terbarukan Berbasis Kombinasi Tempurung Kelapa, Kulit Singkong dan Kulit Jagung - Hutauruk, Ade; Jahra, Alvia; Frahmawati , Cahyani; Angeline , Adinda Martha; Atunia; Yoga; Adelia, Kadek Ayu Cintya (Magnetic: Research Journal of Physics and It’s Application, 2026)
The quality of biomass briquettes is largely determined by the type of raw material and the manufacturing process, especially in efforts to develop waste-based alternative fuels. This research analyzes the effect of the combination of coconut shells with cassava skins and corn husks on the physical properties and burning rate of briquettes using tapioca flour adhesive. Test results show that variations in biomass produce significantly different combustion characteristics. Cassava husk–coconut shell based briquettes showed a higher combustion rate (0.24 g/minute), while corn husk–coconut shell briquettes produced more stable combustion with a lower rate (0.17 g/minute). Even though the water content of the two briquettes is still within acceptable limits, the high ash content (>25%) is the main limiting factor because it does not meet the SNI 01-6235-2000 standard and has the potential to reduce energy efficiency. These findings confirm that the selection of biomass type and control of the carbonization process play a crucial role in determining the performance of briquettes. Optimizing production parameters is needed so that agricultural waste-based biomass briquettes can be developed as an alternative fuel that meets national quality standards and supports a sustainable energy transition.